SISTEM INFORMASI PARTAI POLITIK - Arifudin SH MH (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2019)
Information systems of political parties (Sipol) as a set of information systems and technologies used to support the work of Political Parties and Election Organizers in registering, administrative research and factual verification of the fulfillment of the requirements of political parties to participate in the elections. But in its application, Sipol actually becomes an obstacle for certain parties to become election participants. In this research, the method used is normative juridical. The result of his research is Sipol is not as the main element in determining the political party to be the eligible participant, especially in the political party which becomes the participant of the election in the previous election. However, Sipol is only a supporter of work for KPU and political parties in completing the registration of political parties as eligible participants.